Planning Approaches to Achieve a More Sustainable Travel Industry for Tourism in the UK - a Case Study - Robbins, Derek; Brackstone, John; Dickinson, Janet (European Journal of Transport and Infrastructure Research, 2011)
Transport is tourism's largest contributor to greenhouse gas (GHG) emissions. In the UK domestic tourism is dominated by car. The UK government is committed to a decrease in carbon emissions and to growing its tourism industry simultaneously. This paper explores the potential conflicts between the transport and tourism policy objectives and evaluates current policies. One obvious approach is to achieve a modal shift away from car to more sustainable public transport. The National Trust operates a large number of tourist attractions in the UK and has attempted to reduce the share of arrivals by car. The paper uses a large sample of visitors to National Trust properties as a case study to measure modal share and identify recent trends. The paper identifies those factors which have the greatest impact on modal choice and evaluates the effectiveness of policies aimed at achieving modal shift. The paper concludes with a discussion outlining the need for a co-ordinated, integrated approach to tourism mobility, highlighting the limitations arising from stakeholders, such as visitor attractions, operating in isolation.